Effect of Metal Ions, Solvents and Surfactants on the Activity of Protease from Aspergillus niger KIBGE-IB36 - Hafsa Sattar; Afsheen Aman; Shah Ali Ul Qader (Journal of Basic & Applied Sciences, 2017)
Metal ions greatly impact on the enzymatic activity, they may form strong interaction by forming coordinate bond with enzyme-substrate at the catalytic site which may activate, inhibit or stabilized the enzyme molecules. In this study, extracellular protease from Aspergillus niger KIBGE-IB36 was precipitated with 40% ammonium sulfate. It was revealed that K+, Ba2+, Na+, Mg2+ Zn2+, Ca2+ boosted the protease activity whereas, Cs+, Mn2+, Cu2+, Ni2+, V2+, Co2+, Hg2+ and Al3+ showed to be inhibitor of protease. Dimethyl sulfoxide (5.0 mM) and methanol (5.0 mM) showed catalytic activity while ethanol at same concentration exhibited inhibitory effect. Protease activity augmented with Tween 80, while SDS, Triton X-100, EDTA and PMSF exhibited inhibitory effect.